Algorithms and discrete applied mathematics : 5th International Conference, CALDAM 2019, Kharagpur, India, February 14-16, 2019, Proceedings /: 5th International Conference, CALDAM 2019, Kharagpur, India, February 14-16, 2019, Proceedings. (2019) - Unknown
No abstract available